Radiating feminism : resilience practices to transform our inner and outer lives - Berila, Beth (New York : Routledge, Taylor & Francis Group, 2021)
"Radiating Feminism: Resilience Practices to Transform our Inner and Outer Lives is a practical guide to embodying feminist principles not just in our politics, but also in our very ways of being. Bringing together intersectional feminism with mindful reflection and embodied practice, this book offers practical wisdom for living by feminist principles in our daily lives. Each chapter includes practices, and interactive activities to help navigate common challenges along feminist journeys. The book also draws on wisdom from feminist leaders; and contemporary conversations from social justice movements. Both inspiring and guiding, the book will provide readers with the skills to cultivate resilience to face the many barriers to feminist social transformation. Radiating Feminism will be of use to students of Gender Studies, Social Work, Psychology, Community Health, and the Social Sciences, as well as anyone with a longstanding or fresh commitment to feminism and social justice"--
OCLC-licensed vendor bibliographic record.
Keywords: Feminism -- History -- 21st century; Resilience (Personality trait); Social change; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Women's Studies